2021
DOI: 10.1186/s12891-020-03915-w
|View full text |Cite
|
Sign up to set email alerts
|

Temporary hemiepiphysiodesis using an eight‐plate implant for coronal angular deformity around the knee in children aged less than 10 years: efficacy, complications, occurrence of rebound and risk factors

Abstract: Background Temporary hemiepiphysiodesis (TH) using an eight-Plate implant is one of the most common surgeries used for the correction of coronal angular deformities around the knee in adolescents. However, few studies have focused on children aged less than 10 years treated with TH using an eight-Plate implant. The purpose of this study was to investigate the efficacy, correction velocity, and complications of TH with an eight-Plate implant as well as the occurrence of rebound and risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
49
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 23 publications
6
49
3
1
Order By: Relevance
“…In fact, many previous studies on temporary hemiepiphysiodesis have reported its varying frequencies and degrees. 4,[7][8][9] As exactly predicting the timing of skeletal maturity is difficult in growing patients, understanding postoperative courses after temporary hemiepiphysiodesis and implant removal is essential for optimal results. However, studies dealing with postoperative courses after implant removal are still rare.…”
mentioning
confidence: 99%
“…In fact, many previous studies on temporary hemiepiphysiodesis have reported its varying frequencies and degrees. 4,[7][8][9] As exactly predicting the timing of skeletal maturity is difficult in growing patients, understanding postoperative courses after temporary hemiepiphysiodesis and implant removal is essential for optimal results. However, studies dealing with postoperative courses after implant removal are still rare.…”
mentioning
confidence: 99%
“…This is consistent with literature showing that younger children with both idiopathic and nonidiopathic genu valgum developed rebound after TBP removal. 7,8 Ramazanov et al 15 reported similar age group results. Also, they had more rebound in cases with femur physes treated by TBP than tibia (femur 60% and tibia 50%).…”
Section: Discussionmentioning
confidence: 69%
“…The published literature is not specific regarding selection of cases for overcorrection. 7,8,15,18 In addition, Leveille et al 9 suggested that surgeons' consider the etiology of lower limb deformity before performing overcorrection; however, they did not give definitive guidelines. From our data, we cannot propose reliable calculations for the prediction of overcorrection versus rebound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations